The production performance of Nile tilapia Oreochromis niloticus and mineral balance in aquaponic, biofloc, and aquabioponic culture systems - Radi Ihlas Albani; Budiardi, Tatag; Yani Hadiroseyani; Julie Ekasari (Indonesian Society of Scientific Aquaculture (ISSA), 2023)
Aquaponics and biofloc are aquaculture techniques for reducing nitrogenous waste with less water exchange. Aquaponics reduces nitrate (NO3-) through the role of vegetable plants, while biofloc assimilates ammonia (NH4+) through the role of floc-forming bacteria. In this study a collaboration was designed between aquaponics and biofloc called aquabioponics. This study was conducted to evaluate the performance of tilapia production, as well as to observe the dynamics of P, K, Ca, Mg, Fe, Mn, Zn, and Cu minerals formed in the system. This study used a completely randomized design with three treatments and three replications, namely aquaponics (AP), biofloc (BF), and aquabioponics (AB). The AP integrates water in fish tank with vegetable, and does not use additional organic carbon sources. BF uses the addition of an organic carbon source, but does not integrate vegetables. Meanwhile, AB uses the addition of an organic carbon source (half of the dose in BF) and also integrates vegetables. Nile tilapia Oreochromis niloticus with a length of 5.56 ± 0.13 cm and a weight of 5.92 ± 0.47 g totaling 200 individuals were monitored for 60 days in a fiber tank containing 500 L of water in each treatment. The vegetables used in the AP and AB are Pok Choi which is harvested every 30 days. In this study, aquabioponics is a system that produces the best tilapia production performance. The minerals Ca, Mg, Mn, Zn, and Cu are thought to be essential in aquaponics and aquabioponics, while Mg is thought to be essential in bioflocs. Keywords: aquaponic, aquabioponic, biofloc, minerals, Nile tilapia ABSTRAK Akuaponik dan bioflok adalah teknik akuakultur untuk mereduksi limbah nitrogen dengan sedikit pertukaran air. Akuaponik mereduksi nitrat (NO3-) melalui peran tanaman sayuran, sedangkan bioflok mengasimilasi amonia (NH4+) melalui peran bakteri pembentuk flok. Penelitian ini merancang kolaborasi antara akuaponik dan bioflok yang disebut akuabioponik. Penelitian dilakukan untuk mengevaluasi kinerja produksi ikan nila, serta mengamati dinamika mineral P, K, Ca, Mg, Fe, Mn, Zn, dan Cu yang terbentuk di dalam sistem. Penelitian ini menggunakan rancangan acak lengkap dengan tiga perlakuan dan tiga ulangan, yaitu akuaponik (AP), bioflok (BF), dan akuabioponik (AB). AP mengintegrasikan air pemeliharaan ikan dengan penanaman sayur, dan tidak menggunakan penambahan sumber karbon organik. BF menggunakan penambahan sumber karbon organik, namun tidak menggintegrasikan sayuran. AB menggunakan penambahan sumber karbon organik (setengah dari dosis pada BF) dan juga mengintegrasikan sayuran. Ikan nila Oreochromis niloticus dengan panjang 5.56±0.13 cm dan bobot 5.92 ± 0.47 g sebanyak 200 ekor dipelihara selama 60 hari pada bak fiber berisi 500 L air di setiap perlakuan. Sayuran pada AP dan AB adalah Pok Choi yang dipanen setiap 30 hari. Pada penelitian ini, akuabioponik merupakan sistem yang menghasilkan kinerja produksi ikan nila terbaik. Mineral Ca, Mg, Mn, Zn, dan Cu diduga esensial pada akuaponik dan akuabioponik, sedangkan pada bioflok mineral yang diduga esensial adalah Mg. Kata kunci: akuaponik, akuabioponik, bioflok, ikan nila, mineral